STANDARDISASI ALUR PELAYANAN TUBERKULOSIS DI PUSKESMAS PEMBANTU KELURAHAN SERANGAN: Program Pengabdian Masyarakat untuk Penguatan Kapasitas Tenaga Kesehatan dalam Penanganan Terduga TB di Denpasar - Wirabuana Putra, Gede; Erma Pradnyani, Putu; Wijaya Widiyanto, Wahyu (APTIRMIKI, 2025)
Tuberculosis (TB) remains a public health challenge in Indonesia with an incidence of 391 per 100,000 population. Kelurahan Serangan Sub-Health Center (Pustu) lacks standardized TB service flow, causing practice variations and suboptimal coordination. This activity aims to improve suspected TB case service quality through evidence-based service flow socialization and standardization. Methods included existing condition analysis, SOP development, socialization and training, guided implementation, and evaluation. Results showed 100% of health workers (6 people) participated in training with 90% satisfaction rate. SOP implementation achieved 85% adherence in daily practice. There was a 45% increase in TB service practice standardization and 35% reduction in inter-staff variations in case management. Coordination with referral facilities improved by 40% through structured communication system implementation. This activity successfully standardized TB service flow and enhanced health worker capacity in TB early detection at primary care level.